Da-Chai-Hu-Tang Protects From Acute Intrahepatic Cholestasis by Inhibiting Hepatic Inflammation and Bile Accumulation via Activation of PPARα - Xu, Shihao; Qiao, Xi; Peng, Peike; Zhu, Ziyi; Li, Yaoting; Yu, Mengyuan; Chen, Long; Cai, Yin; Xu, Jin; Shi, Xinwei; Proud, Christopher G.; Xie, Jianling; et al. (Frontiers in Pharmacology, 2022)
Cholestasis is caused by intrahepatic retention of excessive toxic bile acids and ultimately results in hepatic failure. Da-Chai-Hu-Tang (DCHT) has been used in China to treat liver and gallbladder diseases for over 1800 years. Here, we demonstrated that DCHT treatment prevented acute intrahepatic cholestasis with liver injury in response to α-naphthylisothiocyanate (ANIT) not to bile duct ligation (BDL) induced-extrahepatic cholestasis. ANIT (80 mg/kg) increased serum levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST), direct bilirubin (DBiL), total bilirubin (TBiL), and total bile acids (TBA) which was attenuated by DCHT treatment in a dose-dependent manner. DCHT treatment at high dose of 1.875 g/kg restored bile acid homeostasis, as evidenced by the recovery of the transcription of genes implicated in bile acid biosynthesis, uptake and efflux. DCHT treatment (1.875 g/kg) reversed ANIT-evoked disordered glutathione homeostasis (as determined by GSH/GSSG ratio) and increased in the mRNA levels for Il6, Il1b and Tnfα associated with liver inflammation. Using network pharmacology-based approaches, we identified 22 putative targets involved in DCHT treatment for intrahepatic cholestasis not extrahepatic cholestasis. Molecular docking data revealed that most of the active compounds from DCHT interact with amino acid residues in the binding site of PPARα. In addition, as evidenced by dual-luciferase reporter assays, compounds from DCHT with high affinity of PPARα increased luciferase levels from a PPARα-driven reporter. PPARα agonist fenofibrate was able to mimic the cytoprotective effect of DCHT on intrahepatic cholestasis, which was abolished by the PPARα antagonist GW6471. KEGG enrichment and western blot analyses showed that signaling axes of JNK/IL-6/NF-κB/STAT3 related to PPARα might be the principal pathway DCHT affects intrahepatic cholestasis. Taken together, the present study provides compelling evidence that DCHT is a promising formula against acute intrahepatic cholestasis with hepatotoxicity which works via PPARα activation.